Innovation Drama Teaching of â€œNew Pinocchioâ€ in Chinese Language Learning: Action Research - Chuo, Mei-Hsiu (PAROLE: Journal of Linguistics and Education, 2019)
The prevalence of learning Chinese in the United States is very popular with the learning Chinese language throughout the world. This atmosphere is very encouraging for children in Chinese schools and improves their learning motivation. This research is action research and the purpose of this study is (1) to explore the current situation of teaching Chinese in the United States and to answer the research questions based on the reaction and self-reflection of young children, (2) to revise teaching materials and teaching methods during the research, (3) to utilize the innovation story theater model into the Chinese curriculum of the bilingual school in USA, and (4) to find out the suggestions and feasible solutions to the various problems. The research found that if learning activities are intrinsically attractive there is no need to arrange any games to motivate children's learning. Moreover, the findings show that the innovative story theater is very practical and can effectively enhance children's interest in learning Chinese